Penegakan Hukum Kasus Tindak Pidana Penggelapan di Wilayah Hukum Kepolisian Resor Ogan Komering Ulu (Polres Oku) - Rinaldy Anugrah Akbar; Ruben Achmad; Cholidi Zainuddin (CV Rewang Rencang, 2024)
The case of embezzlement or human crime is a very serious case and the perpetrators should be punished as severely as possible. There are inhibiting factors such as laws and regulations, law enforcement officers and public awareness. This type of research is empirical juridical supported by library data and related laws and regulations. The specification of this research is descriptive analytical, the data used is primary data and secondary data sourced from primary, secondary and tertiary legal materials. Based on the results of the study, it was found that law enforcement in cases of embezzlement in the jurisdiction of the OKU Police was carried out through prevention efforts with non-penal means with a restorative justice (RJ) approach and crime prevention with penal means or using criminal law means.